Ellis-van Creveld Syndrome: A Rare Clinical Report of Oral Rehabilitation by Interdisciplinary Approach - Talib Amin Naqash; Ibrahim Alshahrani; Siripan Simasetha (Case Reports in Dentistry)
Ellis-van Creveld syndrome (EVC) is a very rare genetic disorder that affects various tissues of ectodermal and mesodermal origin; patients with EVC present with typical oral deficiencies. The affected individuals are quite young at the time of oral evaluation. It is, therefore, important that these individuals are diagnosed and receive dental treatment at an early age for their physiologic and psychosocial well-being. Albeit there are numerous articles penned on the EVC, the treatise from an oral perspective is inadequate, covering only oral exhibitions and the preventive treatments. This article reviews the literature and serves as the first disquisition for oral rehabilitation of an EVC patient utilizing surgical, orthodontic, restorative, and prosthodontic management.